Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/dc.23694
|View full text |Cite
|
Sign up to set email alerts
|

Adult ocular medulloepithelioma diagnosed by transscleral fine needle aspiration: A case report

Abstract: Ocular medulloepithelioma (ME) is a rare congenital tumor which occurs usually during childhood but is also reported in adults. They have seen an intraocular tumor in an 89 years-old female with a history of small cell lung carcinoma. Transscleral fine needle aspiration was performed. Aspirates were rich and composed of two distinctive populations of cells. The first consisted of epithelioid large cohesive cells with rare rosettes. Nuclei were oval and chromatin was delicate with small nucleoli. The second pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…Novel molecular genetic methods, like liquid biopsies of tumor-derived cellfree DNA from aqueous fluid for prognostication and from plasma for prenatal testing and detection of nonocular primary malignancies in children with retinoblastoma, are discussed [50][51][52]. Coverage of diagnostic cytopathology for tumors of the retina and neuroepithelium is a notable addition (Table 10) [2,[53][54][55][56][57][58][59][60].…”
Section: Tumors Of the Uveal Tract (Table 7)mentioning
confidence: 99%
“…Novel molecular genetic methods, like liquid biopsies of tumor-derived cellfree DNA from aqueous fluid for prognostication and from plasma for prenatal testing and detection of nonocular primary malignancies in children with retinoblastoma, are discussed [50][51][52]. Coverage of diagnostic cytopathology for tumors of the retina and neuroepithelium is a notable addition (Table 10) [2,[53][54][55][56][57][58][59][60].…”
Section: Tumors Of the Uveal Tract (Table 7)mentioning
confidence: 99%
“…Although rare, the possibility of seeding malignant cells outside the eye after tumor's biopsy is of special concern, and some authors suggested that the risk of tumor seeding in medulloepithelioma biopsy should default to the risk-equivalent of retinoblastoma, until more information is available. Nonetheless, in some previous cases, FNAB was used to provide histologic confirmation of medulloepithelioma diagnosis [6,18,[22][23][24][25]. Additionally, it is well-known that both resection with safety margins and radiotherapy or radiofrequency application after biopsy, may prevent the risk of malignant cell seeding in some extra-ocular tumors [26][27][28].…”
Section: B Amentioning
confidence: 99%
“…В нашем исследовании у четырех пациентов из девяти опухоль выявлена в возрасте старше 10 лет. МЭ у взрослых пациентов (старше 20 лет) относится к крайне редким образованиям, и в литературе описаны лишь единичные случаи данной патологии во взрослом возрасте [15][16][17][18][19]. МЭ необходимо дифференцировать от приобретенной эпителиомы (аденомы или аденокарциномы) беспигментного цилиарного эпителия, развивающейся во взрослом возрасте и не имеющей признаков эмбрионального новообразования [21].…”
Section: результатыunclassified
“…Средний возраст манифестации заболевания составил 44 года (в диапазоне 23-79 лет), пятерым пациентам диагноз был поставлен на пятой декаде их жизни. В большинстве случаев был отмечен существенный временной промежуток между проявлением первых симптомов и установлением диагноза [7,8,[15][16][17][18][19].…”
unclassified